Elbow Uncemented Hemiarthroplasty: Surgical Technique - Colin H. Beckwitt, MD, PhD; Emerald D. Robertson, BS; Ja Hea Gu, MD, PhD; Maria M. Munsch, MD; Mark E. Baratz, MD; Robert A. Kaufmann, MD (Journal of Hand Surgery Global Online, 2024)
Management of elbow arthritis in younger and higher demand patients is challenging and may benefit from a distal humerus hemiarthroplasty that employs a noncemented method of implant fixation and stabilizes the elbow through ligament reconstruction. By not replacing both articulating surfaces, hardware longevity may be improved. We describe a novel system that may be indicated for the treatment of posttraumatic or primary osteoarthritis of the distal humerus. The step-by-step technique for surgical implantation of this uncemented distal humerus hemiarthroplasty is described and illustrated.